The Promotion of Collective Bargaining: Different Models - Belcher, Vanessa (Department of Public Law, 2024)
The process of collective bargaining emerged as a consequence of the Industrial Revolution. It was developed as way in which workers could act together in order to attain greater bargaining power and protect their interests and job security more effectively. The process was initially very unpopular as it was seen as a threat to an employer's ability to make profit and as a process which contravened basic contractual principles. However, over time perceptions started to change and collective bargaining became more acceptable. Its popularity gradually grew and collective bargaining eventually became a standard feature of industrial relations systems in many industrialised market economies across the world. In fact its recognition, implementation and promotion have become so widespread in modern times that the bargaining process can be accurately described as a global phenomenon.